Press-braked stainless steel channel section columns failing by flexural buckling : testing, numerical simulation and design - Zhang, Lulu (2022)
The minor-axis flexural buckling behaviour and strengths of pin-ended press-braked stainless steel channel section columns have been investigated in the present paper through laboratory testing and numerical modelling. An experimental programme was firstly conducted, and included initial global and local geometric imperfection measurements and twelve pin-ended column tests about the minor principal axis. The key obtained test results, including the failure loads, the mid-height lateral deflections at the failure loads, the load–mid-height lateral deflection curves and the failure modes, were reported and discussed in detail. The experimental programme was followed by a numerical modelling programme; finite element models were developed to simulate the test responses and then adopted to perform parametric studies to generate further numerical data on press-braked stainless steel channel section columns over a wide range of cross-section dimensions and member effective lengths. The obtained experimental and numerical data were employed to assess the accuracy of the relevant design rules for press-braked stainless steel channel section columns failing by flexural buckling about the minor principal axis, as given in the European code, American specification, Australian/New Zealand standard and SCI design manual. The results of the assessment indicated that (i) the European code yields unsafe flexural buckling strength predictions for those relatively short and intermediate press-braked stainless steel channel section columns with member non-dimensional slendernesses less than around 1.0, (ii) the American specification leads to unsafe predictions of flexural buckling strength for press-braked stainless steel channel section columns over the whole considered range of member non-dimensional slendernesses up to 3.0, and (iii) the Australian/New Zealand standard and the SCI design manual result in lower levels of design accuracy than the European code and American specification, but with significantly reduced number of unsafe flexural buckling strength predictions.